A Reconsideration of the Construction Period of the Cruciform Terraces and the Elevated Causeways in the Angkor Monuments, Based on the Magnetic Susceptibility of the Sandstone Blocks*. (17th September 2012) - Uchida, E.; Sato, K.; Cunin, O.; Toyouchi, K.
<x xml:space="preserve">Abstract</x> In this paper, the construction period of the cruciform terraces with columns and the elevated causeways in the Angkor monuments of Cambodia is reconsidered, based on the results of our investigation of magnetic susceptibility and other characteristics of sandstone blocks. From an art‐historical point of view, they are generally considered as modifications in the post‐Bayon style period—the period during the reign of Jayavarman VIII (1243–95 ce) or later. However, from a lithological point of view, the average magnetic susceptibilities of the sandstone blocks in the cruciform terraces with columns and the elevated causeways are consistent with the rest of the monument. In addition, the characteristics of the sandstone blocks in the cruciform terraces, such as their shape, the orientation of the bedding plane and the stacking method, suggest that they were constructed in the same period as the rest of the monument.